Experimental study on cyclic performance of steel-hollow core partially encased composite spliced frame beam. Issue 163 (December 2022) - Huang, Hua; Yao, Yifan; Liang, Cunjun; Ye, Yanxia
Abstract: Novel frame beams differ from the traditional steel-concrete composite frame beam, named as steel-hollow partially encased composite spliced frame beam (SHSFB) and steel-partially encased composite spliced frame beam (SPSFB) is proposed herein. SHSFB and SPSFB are "false steel-concrete composite structures", actually, they are regarded as steel structure in mechanism analysis. Plastic hinge is located on the stub beam, while the mid-span of the beam is a steel-concrete composite beam. Their deformation and bearing capacity are similar to that of the steel structures. The novel frame beams also have the advantages of easy construction, steel saving, and good lateral stiffness. In order to study the seismic performance of the novel structures, five specimens were tested under cyclic loading. All specimens showed excellent seismic capacity. When the stub beam was long, its hysteretic curve was more similar to that of the steel frame beam; when the stub beam was short, the ductility, energy dissipation capacity, and drift ratio of the specimen were better, especially for SHSFB. In addition, the flexural capacity of the novel frame beam was calculated. According to the test results and analysis, the thickness of independent beam flange, filling amount of concrete, and length of stub beam are optimized. Highlights: "False steel-concrete composite structures" is proposed. SHSFB and SPSFB are two types of the novel frame beams. The hysteretic capacity of the novel structures was investigated through the tests. Calculation formulas for bearing capacities have been proposed. The optimal design was given according to the experiment results and analysis.